Onychomycosis due to opportunistic molds - Erick Obed Martínez-Herrera; Stefanie Arroyo-Camarena; Diana Luz Tejada-García; Carlos Francisco Porras-López; Roberto Arenas (Sociedade Brasileira de Dermatologia, 2015)
Abstract BACKGROUND: Onychomycosis are caused by dermatophytes and Candida, but rarely by non- dermatophyte molds. These opportunistic agents are filamentous fungi found as soil and plant pathogens. OBJECTIVES: To determine the frequency of opportunistic molds in onychomycosis. METHODS: A retrospective analysis of 4,220 cases with onychomycosis, diagnosed in a 39-month period at the Institute of Dermatology and Skin surgery "Prof. Dr. Fernando A. Cordero C." in Guatemala City, and confirmed with a positive KOH test and culture. RESULTS: 32 cases (0.76%) of onychomycosis caused by opportunistic molds were confirmed. The most affected age group ranged from 41 to 65 years (15 patients, 46.9%) and females were more commonly affected (21 cases, 65.6%) than males. Lateral and distal subungual onychomycosis (OSD-L) was detected in 20 cases (62.5%). The microscopic examination with KOH showed filaments in 19 cases (59.4%), dermatophytoma in 9 cases (28.1%), spores in 2 cases (6.25%), and filaments and spores in 2 cases (6.25%). Etiologic agents: Aspergillus sp., 11 cases (34.4%); Scopulariopsis brevicaulis, 8 cases (25.0%); Cladosporium sp., 3 cases (9.4%); Acremonium sp., 2 cases (6.25%); Paecilomyces sp., 2 cases (6.25%); Tritirachium oryzae, 2 cases (6.25%); Fusarium sp., Phialophora sp., Rhizopus sp. and Alternaria alternate, 1 case (3.1%) each. CONCLUSIONS: We found onychomycosis by opportunistic molds in 0.76% of the cases and DLSO was present in 62.5%. The most frequent isolated etiological agents were: Aspergillus sp. and Scopulariopsis brevicaulis.